Práticas sócio-ambientais no espaço escolar: uma reflexão sobre a percepção dos usuários de duas escolas do ensino fundamental em João Pessoa, Paraíba - Taveira, Flávia Giangiulio (2008)
﻿In the social-historical moment we live in, it is each time more evident the necessity of the people to learn to deal with the environment in conscientious way, taking care of themselves properly through it. In this direction, considering the school as a place where children, young and adolescents spend great part of their time, this work had as objective to examine the perception of school environment for students, professors and employees of two schools in João Pessoa city - Centro Estadual Experimental de Ensino-Aprendizagem Sesquicentenário and Escola Estadual de Ensino Fundamental e Médio Presidente Emílio Garrastazu Médici (Experimental State Center of Learning-teaching Sesquicentenário and Basic and High State School Education Emilio Garrastazu Médici President). From the presupposed that the environments in which and with which people live reflect their daily practices, the field work searched to identify the social-environmental practices that characterize the relation of these users with the school and, from this understanding, to infer some of their concerns regarding the environment as a whole. To analyze the use of the available physical space in the two institutions it was opted the use of the After-Occupation Evaluation, one of the approaches that feed the process of building production or built set, rescuing aspects related to its use, operation and maintenance. Besides analyzing diverse school environments (such as classroom circulations/accesses, library, pedagogical and sportive spaces) in relation to the environmental comfort and the perceptions of the main users of the schools (pupils, professors and employees), the dissertation tried to inquire the care (ambient education) of these users with the school space. In general, it was verified that the two schools have evaluations and perceptions really different for four reasons: (i) management of the schools; (ii) the users perception; (III) localization of schools and (IV) feeling of place, territoriality and appropriation